Not all respiratory infections were SARS-CoV-2 during the pandemic, analysis in a clinic on the Colombian Caribbean coast - Mara Judith García Posada; Heriberto Jose Cabrales Dajil; Angie Paola Narvaez Díaz; Jose Daniel Del Castillo Vidal; Daniela De Jesus Sierra Barreto; Maria Camila Sanchez; Hector Serrano Coll; Salim Mattar (Elsevier, 2023)
Introduction: Acute Respiratory Infections (ARIs) are considered one of the leading causes of morbidity and mortality worldwide. Children under five and older adults are most likely to die from this cause. Objective: To describe the behavior of infection by respiratory viruses other than SARS-CoV-2 during the pandemic in a clinic in the Colombian Caribbean. Methods: This descriptive and retrospective study evaluates the characteristics, associated comorbidities, and requirements of hospitalization or Intensive Care Unit in patients diagnosed with respiratory viral infections treated at IMAT Oncomedica clinic from July 2020 to August 2022. Results: This study evaluated 351 patients with respiratory symptoms, observing an exponential increase in cases of respiratory infection as of April 2022, with a high proportion of syncytial virus infections mainly in children under 18 years of age (22.1%) and Human Rhinovirus/Enterovirus in patients with solid tumors and hematological disorders (48.8%), the latter was associated with a higher rate of hospitalization and ICU requirement in the individuals evaluated. Conclusions: Respiratory viruses other than SARS-CoV-2, such as Rhino/Enterovirus, RSV, and adenovirus, are circulating in the population at a clinic on the Colombian Caribbean coast. The findings should motivate public health authorities to conduct more thorough surveillance in the rest of the state.